Microstructural evaluation and recommendations for face masks in community use to reduce the transmission of respiratory infectious diseases - Karakoç, Alp; Miettinen, Arttu; Sözümert, Emrah; Evans, Llion; Yiğitler, Hüseyin; Bostanci, Başak; Taciroğlu, Ertuğrul; Jäntti, Riku (Computer Methods and Programs in Biomedicine, 2022)
Background and objectives: Recommendations for the use of face masks to prevent and protect against the aerosols (≤5µm) and respiratory droplet particles (≥5µm), which can carry and transmit respiratory infections including severe acute respiratory syndrome coronavirus (SARS-CoV-2), have been in effect since the early stages of the coronavirus disease 2019 (COVID-19). The particle filtration efficiency (PFE) and air permeability are the most crucial factors affecting the level of pathogen transmission and breathability, i.e. wearer comfort, which should be investigated in detail. Methods: In this context, this article presents a novel assessment framework for face masks combining X-ray microtomography and computational fluid dynamics simulations. In consideration to their widespread public use, two types of face masks were assessed: (I) two layer non-woven face masks and (II) the surgical masks (made out of a melt-blown fabric layer covered with two non-woven fabric layers). Results: The results demonstrate that the surgical masks provide PFEs over 75% for particles with diameter over 0.1µm while two layer face masks are found out to have insufficient PFEs, even for the particles with diameter over 2µm (corresponding PFE is computed as 47.2%). Thus, existence of both the non-woven fabric layers for mechanical filtration and insertion of melt-blown fabric layer(s) for electrostatic filtration in the face masks were found to be highly critical to prevent the airborne pathogen transmission. Conclusions: The present framework would assist in computational assessment of commonly used face mask types based on their microstructural characteristics including fiber diameter, orientation distributions and fiber network density. Therefore, it would be also possible to provide new yet feasible design routes for face masks to ensure reliable personal protection and optimal breathability.
Keywords: Airborne pathogen; COVID-19; Computational fluid dynamics; Face masks; SARS-CoV-2; X-ray microtomography